Odontoblast layer structure alteration as a response to carious lesions - Tetiana Haniastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Dental caries is a bacterial disease affecting the hard tissue of the teeth as well as the pulp. The human dental pulp consists of odontoblast which are organized as a densely packed cell layer. Odontoblasts is located at the periphery of the pulp; therefore, they are the first cells encountered by cariogenic bacteria and their products that are represented in the carious lesion. Purpose: This study aimed to elucidate the effect of cariogenic bacteria to odontoblasts of human teeth. Methods: Five intact third molars and 15 third molars with occlusal caries at various stages of decay were extracted because of orthodontic or therapeutic reasons. The tooth specimens were fixed, decalcified with 10% EDTA solution (pH 7.4), and embedded in paraffin. Serial sections of 5 μm thickness were cut and stained with haematoxylin eosin and Gram’s, in addition to nestin immunohistochemistry. The specimens were then examined under light microscopy. Results: In normal teeth, odontoblast layer were aligned along the pulp chamber showing normal morphology of the cells. Slight disorganization of odontoblast layer was seen in the cases of carious lesions confined to enamel. In the cases of carious lesions confined to dentin, odontoblast layer was not observed in the areas subjacent to the lesions, only single cells showing flattened cell morphology were found. Odontoblasts beneath the lesion suffered severe damage and diminished nestin immunoreaction were observed in all cases of carious lesions with pulp exposure. Conclusion: Cariogenic bacteria invasion may damage the odontoblasts by affecting the morphology and vitality of the cells. The severity of the damage of the odontoblasts may increase as the bacterial invasion progresses toward the pulp.Latar belakang: Karies merupakan penyakit yang disebabkan oleh bakteri, yang dapat memengaruhi jaringan keras gigi maupun pulpa. Pada pulpa gigi manusia terdapat sel odontoblas yang tersusun atas lapisan sel. Odontoblas terletak pada tepi kamar pulpa, sehingga sel ini merupakan sel yang pertama kali bertemu dengan bakteri kariogenik dan produk-produknya yang terdapat dalam lesi karies. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh invasi bakteri kariogenik terhadap sel odontoblas gigi manusia. Metode: Lima buah gigi molar ketiga utuh dan 15 gigi molar ketiga yang mengalami karies pada permukaan oklusal dengan berbagai tingkat keparahan diekstraksi karena akan menjalani perawatan ortodontik atau perawatan lainnya. Gigi-geligi tersebut kemudian difiksasi, didekalsifikasi dengan larutan EDTA 10% (pH 7,4), dan ditanam dalam parafin. Spesimen gigi tersebut kemudian dipotong dengan ketebalan 5 μm dan diwarnai dengan hematoksilin eosin dan Gram, serta immunohistokimia dengan nestin. Spesimen kemudian diamati di bawah mikroskop cahaya. Hasil: Pada gigi normal, lapisan odontoblas terdapat di sepanjang tepi kamar pulpa dengan morfologi sel normal. Disorganisasi ringan pada lapisan odontoblas tampak pada kasus-kasus karies dengan kedalaman enamel. Pada kasus-kasus lesi karies dengan kedalaman dentin, lapisan odontoblas tidak tampak pada daerah di bawah lesi, hanya ditemukan sel odontoblas tunggal dengan dengan morfologi sel yang pipih. Odontoblas di bawah lesi mengalami kerusakan yang parah dan tidak menunjukkan nestin immunopositif merupakan gambaran dari kasus-kasus karies dengan pulpa terbuka. Kesimpulan: Invasi bakteri kariogenik dapat menyebabkan kerusakan sel odontoblas dengan menyebabkan perubahan morfologi dan memengaruhi vitalitas selnya. Kerusakan sel akan semakin parah dengan semakin dalam invasi bakteri ke arah pulpa.